Artificial Creativity: Augmenting Human Professionals - Impuscatu, Roland Mihai (Acta Universitatis Danubius. Communicatio, 2024)
Abstract: This study examines the impact of artificial intelligence (AI) and generative artificial intelligence (GAI) on the advertising industry, with a particular focus on how these technologies are transforming creative processes. AI and AGI offer new opportunities for predicting consumer behavior and generating innovative content, thereby optimizing both the efficiency and costs associated with advertising campaigns. The study explores the applicability of AI and GAI I in various stages of an advertising campaign, from the initial concept to the evaluation of the impact on the target audience. It also discusses the challenges and limited creativity of GAI compared to human creativity, while emphasizing its role in augmenting work processes. The study suggests that the integration of AI and GAI in advertising has considerable potential to reshape the creative landscape, but requires careful collaboration between technologists and practitioners to fully realize the benefits.